Lignin-based rigid polyurethane foams with improved biodegradation - Cateto, C.A. (2014)
Rigid polyurethane (RPU) foams have been synthesized using lignin-based polyols obtained by oxypropylation of four distinct lignins (Alcell, Indulin AT, Curan 27-11P, and Sarkanda). Polyol formulations with two lignin/propylene oxide/catalyst content (L/PO/C) ratios were chosen (30/70/2 and 20/80/5). RPU foams have been prepared with a polyol component that incorporates the lignin-based one at contents ranging from 25 to 100%. A 100% commercial polyol-based (Lupranol! 3323) RPU foam was also prepared and used as the reference. RPU foams were characterized in terms of density, compressive modulus, and conductivity. Cell morphology and size estimation were accessed by scanning electron microscopy. Moreover, biodegradation of the Alcell- and Indulin AT-based foams was evaluated using respirometry tests in liquid and solid media. The Alcell- and Indulin AT-based polyols together with the 20/80/5 Curan 27-11P-based one led to RPU foams with properties quite similar to those of the reference homolog. Biodegradation seems to be, particularly, favored if using Indulin AT-based polyols mixed with Lupranol! 3323.